UTILIZATION OF CHLORHEXIDINE IN PROPHILACTIC TECHNIQUES OF PROFESSIONAL HYGIENIZATION - Cristian Marin; Radu Costea (Romanian Society of Oral Rehabilitation, 2015)
The present clinical study evaluates the results obtained by the application of the classical methods of professional hygienization through ultrasonic scaling, brushing, air flow, comparatively with the additional contribution brought about by chlorhexidine (CHX). The study was developed on a group of 328 subjects, equally divided into a reference, respectively an experimental group. Each group was subdivided into a batch of subjects affected with gingivitis, respectively a batch with persons suffering from periodontopathies. Each patient belonging to the reference group was subjected to professional hygienization, namely scaling with ultrasounds, professional brushing, fluorization, while the subjects forming the experimental group benefited from an additional application of chlorhexidine - in the form of a 1% concentrated gel - inside the subgingival ditches and interdental spaces.